Description of Dysdera zonsteini n. sp. (Arachnida: Araneae: Dysderidae) from Turkmenistan - Dimitrov, Dragomir (Zootaxa, 2021)
A new species of Dysdera Latreille, 1804 is described from the South-Western Kopet Dagh, Turkmenistan, on the basis of both sexes. The species is compared to its closest congener Dysdera kronebergi Dunin, 1992, and tentatively assigned to the D. asiatica species-group.